Experimentally Induced Endometritis Impairs the Developmental Capacity of Bovine Oocytes. Issue 3 (13th May 2020) - Dickson, Mackenzie J; Piersanti, Rachel L; Ramirez-Hernandez, Rosabel; de Oliveira, Eduardo Barros; Bishop, Jeanette V; Hansen, Thomas R; Ma, Zhengxin; Jeong, Kwang Cheol C; Santos, Jose E P; Sheldon, Martin I; Block, Jeremy; Bromfield, John J
Abstract: Uterine infection is associated with infertility in women and dairy cows, even after the resolution of infection. However, the mechanisms causing this persistent infertility are unclear. Here, we hypothesized that induced endometritis in non-lactating dairy cows would reduce the developmental competence of oocytes. Non-lactating Holstein cows received an intrauterine infusion of endometrial pathogenic bacteria ( Escherichia coli and Trueperella pyogenes ; n = 12) or vehicle control ( n = 11) on day 2 of the estrous cycle. Bacterial infusion increased expression of endometrial inflammatory mediators, and a mucopurulent discharge in the vagina confirmed the establishment of endometritis. Oocytes were collected by transvaginal ultrasound-guided ovum pickup on days 2, 24, 45, and 66 following infusion and subjected to in vitro fertilization and embryo culture. Bacterial infusion resulted in fewer cleaved oocytes developing to morulae compared to vehicle-infused controls (30.7 versus 45.0%), with the greatest effect observed in oocytes collected on day 24. Development to morula was inversely correlated with endometrial expression of IL6 on day 6. The expression of genes associated with embryo quality did not differ significantly between morulae from bacteria-infused and control cows. Artificial insemination 130 days after intrauterine infusion resulted in normal, filamentous embryos that produced interferon tau 16 days after conception in both infusion groups. This model of experimentally induced uterine infection successfully resulted in endometritis and a reduction in the proportion of oocytes that developed to morulae following in vitro fertilization. In conclusion, endometritis reduced the capacity of oocytes to develop to morulae. Abstract : Induction of uterine infection has a long-term impact on the oocyte, reducing the capacity of the oocyte to develop to an embryo in dairy cows. Graphical Abstract: